2006
DOI: 10.1144/jm.25.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Trouble in Paradise? A comparison of 1953 and 2005 benthonic foraminiferal seafloor assemblages at the Ibis Field, offshore eastern Trinidad, West Indies

Abstract: Foraminiferal communities are not static, but change in response to environmental perturbations. Given sufficient time, the change will be recorded in the total (live+dead) seafloor assemblage, from which valuable information regarding environmental trends can be obtained by re-sampling assemblages at the decadal scale.The seafloor assemblage in the 5 km 6 km Ibis Field, off southeast Trinidad, first surveyed in 1953, was re-examined in 2005. The fauna had changed markedly between the surveys. Overall increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
0
13
1
Order By: Relevance
“…It might also be argued that, for sections that commence in recent deposits, like those penetrated by many oil wells or piston cores, such a top-down approach will proceed from the known, modern environment and into the unknown. This argument might also be applied to Trinidad's stratigraphic history; much is known of the modern Orinoco delta (van Andel, 1967;Aslan et al, 2003) and of its impact on the modern foraminiferal fauna (Drooger and Kaasschieter, 1958;van der Zwaan and Jorrisen, 1991;Wilson, 2006a). It is, thus, in theory at least, easier to interpret the younger, deltaic deposits of the Manzanilla Formation than the older sediments deposited in other environments.…”
Section: Cipero Formationmentioning
confidence: 99%
“…It might also be argued that, for sections that commence in recent deposits, like those penetrated by many oil wells or piston cores, such a top-down approach will proceed from the known, modern environment and into the unknown. This argument might also be applied to Trinidad's stratigraphic history; much is known of the modern Orinoco delta (van Andel, 1967;Aslan et al, 2003) and of its impact on the modern foraminiferal fauna (Drooger and Kaasschieter, 1958;van der Zwaan and Jorrisen, 1991;Wilson, 2006a). It is, thus, in theory at least, easier to interpret the younger, deltaic deposits of the Manzanilla Formation than the older sediments deposited in other environments.…”
Section: Cipero Formationmentioning
confidence: 99%
“…Second, WILSON (2006d) concluded that the rate of organic matter input to the Ibis Field has increased markedly over the past few decades. Mixing across fronts, however, is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Finding marked increases in the proportional abundances of Uvigerina subperegrina, Pseudononion atlanticum and Rolhausenia rolhauseni, he concluded that the Ibis Field has over recent decades been subjected to an increased organic matter loading. WILSON (2006d) nevertheless concluded that the cause was to be sought in northern South America, perhaps being associated with shrimp farms, unregulated sewer systems, or run-off from sugar plantations. SEN GUPTA eta[.…”
Section: Hydrography Of the Eastern Caribbean And Its Implications Fomentioning
confidence: 99%
See 1 more Smart Citation
“…biofacies. Wilson (2006b) surveyed the 2005 benthonic foraminiferal fauna from the Ibis Field, about 50 km due west of the Savonette Field. Given the distance between Drooger & Kaasschieter's (1958) transects and the Savonette region, however, these percentages must be regarded as approximate only.…”
Section: Previous Workmentioning
confidence: 99%